Determination and Analysis of Trace Elements in Five Kinds of Traditional Chinese Medicine in High Blood Pressure Medicinal Food by ICP-AES - Li Yang; Qinghua Yan; Huixuan Zhang; Jianwei Zhang (Journal of Chemistry)
Objective. To establish a method for analysis of microelements in five kinds of traditional Chinese medicine in high blood pressure medicinal food, mainly including manganese, cobalt, selenium, iron, magnesium, and other 15 elements. Methods. The samples were digested using a microwave digestion instrument through NHO3-H2O2 solution, and then, the elements were synthesized by inductively coupled plasma atomic emission spectrometry (ICP-AES). Results. The content of cobalt, manganese, zinc, copper, and nickel in the high blood pressure diet foods is higher, the RSD is between 0.005% and 4.82%, and the recovery rate ranges from 93.40% to 106.5%. The precision and recovery of the detection method are higher. Conclusion. The experiment result is better. Medicinal foods curing high blood pressure contain a number of micronutrients that are beneficial to the human body. This experiment provides some meaningful basis for the prevention and treatment of cardiovascular diseases such as hypertension.